Factors Supporting Volleyball Athlete Performance in Junior High School Athlete in Bandung District - Dhena Gumelar; Ricky Wirasasmita; Sony Hasmarita (Journal of Physical and Outdoor Education, 2026)
Research based on observations made by researchers, although athletes undergo routine training during extracurricular volleyball training, there are still differences in the achievement of their performance. Formulation of the problem, what supporting factors affect the performance of volleyball athletes in junior high school athletes in Bandung Regency? Research using the survey method. A sample of 25 athletes active at the State Junior High School 2 Banjaran was selected through purposive sampling technique from a total population of 100 volleyball extracurricular members. Data were collected using a questionnaire which has two indicators, namely intrinsic and extrinsic. The analysis technique used in this study is the frequency distribution analysis technique, which is obtained in the supporting factors with a high category of 72%, a very high category of 20%, and a moderate category of 8%. In conclusion, the performance of SMPN 2 Banjaran athletes in Bandung district is influenced by supporting factors in intrinsic and extrinsic aspects with high categories. Which means that the supporting factors of both intrinsic and extrinsic aspects can significantly affect the performance of volleyball athletes at SMPN 2 Banjaran athletes in Bandung Regency. Factors from within (intrinsic by 88%) include physical condition, tactics, tactics, psychological and nutrition, while factors from outside (extrinsic by 88%) include the support of the closest people and the availability of training facilities.